Supercapacitor materials: From research to the real world - Nawaz A.; Pandey V.K.; Kumar P. (My University, 2025)
Supercapacitors are gaining prominence in the realm of energy storage devices due to their high power density, extended cycle stability, and fast charge/discharge rates. Supercapacitors are widely used in industries such as service grids, transportation, consumer electronics, wearable and flexible systems, energy harvesting, etc. Due to their remarkable high-power performance, high reliability, and extended lifetime, they are a key electrochemical device for energy storage; as a result, the worldwide supercapacitor market is rapidly developing. Supercapacitors have a straightforward basic construction, but different products for various applications require cells in various configurations. The application of supercapacitors from the perspective of the industry is the subject of this chapter. © 2024 Bentham Science Publishers. All rights reserved.